2021
DOI: 10.7196/ajhpe.2021.v13i2.1246
|View full text |Cite
|
Sign up to set email alerts
|

Improving South African medical curricula related to traditional health systems

Abstract: An unexamined educationSouth African (SA) medical curricula on traditional health systems remain a largely unexamined topic, despite millions of South Africans using traditional healthcare daily. Chitindingu et al. 's [1] 2014 study outlined the major formal elements of the traditional healing curricula, as described by administrators at each of SA's eight medical schools. Our study aims to answer their call for better understanding of this topic from the perspective of medical students' experience of the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This finding contradicts a recent study which includes South Africa as one of the countries in Sub-Saharan Africa that provide formal TM education [ 58 ]. Other research has reported AM students training at various universities in South Africa requesting training that includes teaching about the fundamentals of TM, how to empathise with patients who use TM, and how to approach such patients during a consultation [ 59 ]. Furthermore, it is acknowledged that the solution entails not only modifying curricula and student understanding but also changing faculty mindsets in this regard [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding contradicts a recent study which includes South Africa as one of the countries in Sub-Saharan Africa that provide formal TM education [ 58 ]. Other research has reported AM students training at various universities in South Africa requesting training that includes teaching about the fundamentals of TM, how to empathise with patients who use TM, and how to approach such patients during a consultation [ 59 ]. Furthermore, it is acknowledged that the solution entails not only modifying curricula and student understanding but also changing faculty mindsets in this regard [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pillay and Kathard (25) described students' exposure to longitudinal community engagement as a means to promote context-specific learning and decolonization of health education. This can also overcome some of the deficits in the content of health sciences curricula that often fail to integrate traditional medicine approaches in the management of African patients and where assessment tools have been developed within a colonial framework and for Eurocentric populations (26).…”
Section: Taking Care To the Peoplementioning
confidence: 99%
“…In Iran, most studies have adopted a qualitative approach to examine the experience of nursing and medical students with the HC [13,14]. However, there has been limited studies on HC upgrade [6,15] as the central topics have been improving the learning environment, tackling the negative effects of the HC, identifying the positive and negative in uences of the HC, facilitating HC learning, and the in uences of the HC in nursing and medical education [8,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%